UTHM Scheduled Waste Management System - Azaman, Farahani; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2022)
UTHM Scheduled Waste Management System is a web-based system that increases UTHM OSHE’s accessibility to all scheduled waste’s information in UTHM. The purpose of developing this prototype is to solve the problem of UTHM OSHE in recording and managing the scheduled waste and disposal application manually using documented system. The users of this system are Pegawai Sains, Pengurus Makmal, Penolong Jurutera, Unit Persekitaran OSHE UTHM, and UTHM OSHE Administration. This system also has four modules which is user registration and login module, scheduled waste registration module, disposal application module and report generation module. Futhermore, this system will be developed through a structural approach by using Incremental Model. The software used in developing this system are Visual Studio Code, MySQL database and programming language Hypertext PreProcessor (PHP). The conclusion is the development of this system will improve the accessibility and manageability of all scheduled waste information in UTHM.